E-Learning: Online Teaching Experiences of Higher Education Teachers in India During the Covid19 Pandemic - Devaki (Hasanuddin University, 2023)
The COVID19 pandemic has compelled teachers to convert their physical classes to online instruction within a brief time-frame. The study’s purpose is to investigate higher education teachers' perceptions and experiences of their online teaching after months of online instruction during the outbreak of pandemic situations and to examine the challenges faced by the teachers in adapting to the online teaching-learning process during the COVID-19 pandemic. The study employs a mixed-method approach to collect data. This method includes both quantitative and qualitative approaches to broaden the scope and intensity of the research. A survey has been conducted and a questionnaire is framed and has been disseminated among higher education teachers across colleges, universities of Tamilnadu and Karnataka. Overall, 194 respondents participated in the survey to express their views and experiences. The survey provided quantitative data, while open-ended questions in the questionnaire offered qualitative insights. The findings illuminate two primary challenges: the teachers' experiences with online teaching during the Covid-19, as well as their lack of knowledge in the online teaching and learning mode—in the survey, the quantitative data analysis highlight two issues: internet connectivity and self-inspection or monitoring. On the other hand, open-ended questions in the questionnaire offered qualitative insights on their perceptions and experiences regarding the easiness and benefit of technology utilization, the usefulness of technology, and also the support they experienced during the transition. the research recommends incorporating specific features into the Learning Management System (LMS). The research proposes blended or hybrid learning should be implemented because e-learning requires a significant amount of self-study or conscience; teachers should develop and provide high-quality e-resources to students, with an in-depth focus on conundrum during online interactive classrooms.